2021
DOI: 10.3390/jcm10235643
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effectiveness of Hypothermic Targeted Temperature Management According to the Severity of Post-Cardiac Arrest Syndrome

Abstract: International guidelines recommend targeted temperature management (TTM) to improve the neurological outcomes in adult patients with post-cardiac arrest syndrome (PCAS). However, it still remains unclear if the lower temperature setting (hypothermic TTM) or higher temperature setting (normothermic TTM) is superior for TTM. According to the most recent large randomized controlled trial (RCT), hypothermic TTM was not found to be associated with superior neurological outcomes than normothermic TTM in PCAS patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Second, hyperoxygenation can promote recovery by enhancing tissue oxygen delivery to ensure organ function and viability (48,49), whereas TTM can attenuate PCAS by reducing the excessive accumulation of ROS and enhancing antioxidant activity (50). Third, the efficacy of hyperoxygenation and TTM is related to etiology when used alone (24,51), whereas the combination can improve tissue oxygen supply accompanied by reduced oxidative stress damage, therefore maximizing treatment effectiveness (14). This is the first study to investigate the effect of hyperoxygenation and TTM on PCAS in both asphyxial and dysrhythmic CA rat models.…”
Section: Discussionmentioning
confidence: 99%
“…Second, hyperoxygenation can promote recovery by enhancing tissue oxygen delivery to ensure organ function and viability (48,49), whereas TTM can attenuate PCAS by reducing the excessive accumulation of ROS and enhancing antioxidant activity (50). Third, the efficacy of hyperoxygenation and TTM is related to etiology when used alone (24,51), whereas the combination can improve tissue oxygen supply accompanied by reduced oxidative stress damage, therefore maximizing treatment effectiveness (14). This is the first study to investigate the effect of hyperoxygenation and TTM on PCAS in both asphyxial and dysrhythmic CA rat models.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, our previous study showed that the treatment effect size was different by score points on the rCAST and that the patient group that is particularly likely to derive benefit from TTM at the lower setting temperature is the group with PCAS of moderate-severity grade on rCAST 23 . Although further research is needed, this may also be applicable to IHCA patients, indicating that the risk classification with the rCAST before TTM may be helpful in identifying IHCA patients who benefit most from TTM at the lower setting temperature 24 .…”
Section: Discussionmentioning
confidence: 99%